Characteristics Of Stress Urinary Incontinence (SUI) Patients In Dr. Mohammad Hoesin General Hospital On 2019 To 2021 - Raisa Sabila; Hadrians Kesuma Putra; Rara Inggarsih (Biomedical Journal of Indonesia, 2022)
Introduction. Stress urinary incontinence (SUI) is a condition where urine comes out accidentally due to intraabdominal pressure increase when sneezing, coughing, laughing, or weightlifting. SUI often occurs in women and has a negative impact on quality of life. However, not many patients visit the hospital for treatment. This research aims to describe the characteristics of SUI patients in Dr. Mohammad Hoesin General Hospital 2019-2021. Methods. This research is a descriptive observational study with a cross-sectional approach using patient’s medical records in Dr. Mohammad Hoesin General Hospital 2019-2021. The sample in this study are 15 samples taken by total sampling. Results. This study found that SUI was common in patients aged 41-60 years (66,7%). The majority of patients were multiparous (93,3%) and had experienced menopause (86,7%). Most of the patients gave birth spontaneously (80,0%), were obese (53,3%), had a duration of the second stage labor >1 hour (60,0%), had given birth to a baby with birth weight ≥3.000 g (80,0%), and has had an episiotomy (73,3%). The majority of SUI patients had no history of neurological disorders (93,3%). Every SUI patients were treated with anterior colporrhaphy (100,0%). Conclusion. SUI often occurs in patients aged 41-60 years, multiparous, menopausal, obese in BMI, has a history of  >1 hour second stage labor, has given birth to a baby with a birth weight ≥3.000 g, and has had an episiotomy. SUI patients at Dr. Mohammad Hoesin General Hospital were treated with anterior colporrhaphy.